Atrial Fibrillation Dynamics and Ionic Block Effects in Six Heterogeneous Human 3D Virtual Atria with Distinct Repolarization Dynamics - Sánchez, Carlos; Bueno-Orovio, Alfonso; Pueyo, Esther; Rodríguez, Blanca (Frontiers in Bioengineering and Biotechnology, 2017)
Atrial fibrillation (AF) usually manifests as reentrant circuits propagating through the whole atria creating chaotic activation patterns. Little is yet known about how differences in electrophysiological and ionic properties between patients modulate reentrant patterns in AF. The goal of this study is to quantify how variability in action potential duration (APD) at different stages of repolarization determines AF dynamics and their modulation by ionic block using a set of virtual whole-atria human models. Six human whole-atria models are constructed based on the same anatomical structure and fibre orientation, but with different electrophysiological phenotypes. Membrane kinetics for each whole-atria model are selected with distinct APD characteristics at 20, 50 and 90% repolarization, from an experimentally-calibrated population of human atrial action potential models including AF remodeling and acetylcholine parasympathetic effects. Our simulations show that in all whole-atria models, reentrant circuits tend to organize around the pulmonary veins and the right atrial appendage, thus leading to higher dominant frequency (DF) and more organized activation in the left atrium than in the right atrium. Differences in APD in all phases of repolarization (not only APD90) yielded quantitative differences in fibrillation patterns with long APDs associated with slower and more regular dynamics. Long APD50 and APD20 were associated with increased inter-atrial conduction block and inter-atrial differences in DF and OI, creating reentry instability and self-termination in some cases. Specific inhibitions of IK1, INaK or INa reduce DF and organization of the arrhythmia by enlarging wave meandering, reducing the number of secondary wavelets and promoting inter-atrial block in all six virtual patients, especially for the phenotypes with short APD at 20, 50 and/or 90% repolarization. This suggests that therapies aiming at prolonging the early phase of repolarization might constitute effective anti-arrhythmic strategies for the pharmacological management of AF. In summary, simulations report significant differences in atrial fibrillatory dynamics resulting from differences in APD at all phases of repolarization.